Host plant resistance in safflower (Carthamus tinctorius L.) to aphid, Uroleucon compositae (Theobald): Host plant resistance in safflower (Carthamus tinctorius L.) to aphid, Uroleucon compositae (Theobald) - V B AKASHE; P B WAKALE; D V INDI; S K SHINDE; L N TAGAD; K C OMBASE (Journal of Oilseeds Research, 2020)
Based on aphid population, foliage drying grades, bio-physical, bio-chemical and yield attributing characters, the resistance of five out of 14 pre-identified aphid tolerant safflower genotypes was confirmed against aphid. Plant morphology plays an important role in the aphid resistance. The phenol and OD phenol contents showed no significant differences between resistant and susceptible genotypes. The safflower entries having more spines, hard thick stem, wiry peduncles, green, thin and waxy leaves, tiny capitula and small sized seeds sheltered less aphid build up. Looking to all the bio-physical and bio-chemical characters along with yield potential, only five more- spiny genotypes viz., SSF-682, SSF-695, SSF-704, SSF-714 and SSF-734 were found most promising and have confirmed resistance against safflower aphid. They may be used in breeding programme for incorporation of aphid resistance.